Meta-analytic cointegrating rank tests for dependent panels - Deniz Dilan Karaman Örsal; Antonia Arsova (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2015)
This paper proposes two new panel cointegrating rank tests which are robust to cross-sectional dependency. The dependence in the data generating process is modeled using unobserved common factors. The new tests are based on a metaanalytic approach, in which the p-values of the individual likelihood-ratio (LR) type test statistics computed from defactored data are combined to develop the panel statistics. A simulation study shows that the tests have reasonable size and power properties in finite samples.
Keywords: C12; C15; C33; 330; panel cointegration; p-value; common factors; rank test; crosssectional dependence